INTERCULTURAL TOLERANCE AS A GOAL OF LANGUAGE EDUCATION IN THE CONTEXT OF GLOBALIZATION - Козак, Алла; Книш, Тетяна; Іванашко, Оксана (SWorldJournal, 2026)
The article focuses on the analysis of intercultural tolerance as an important component of modern language education in the context of globalization. The purpose of the study is to determine the essence, structural components, and pedagogical conditions